An investigation into the role and effects of the endocannabinoid system in adipocytes - Cable, Jemma (2012)
In recent years evidence has emerged that the endocannabinoid system (ECS) may have a significant role in metabolism and energy homeostasis. Several studies have identified upregulation of the peripheral ECS in obesity and type 2 diabetes, but the mechanisms behind this and the consequences of upregulation are unclear. The aim of this thesis was to further elucidate the role of the ECS in mature adipocytes, and its activity in obesity and related metabolic dysfunction. Three adipose tissue depots were dissected from lean, obese and obese diabetic Zucker rats (n=6-8). In human studies, written informed consent was obtained from healthy volunteers within the University of Nottingham and obese surgical patients at the Royal Derby Hospital. Anthropometric measurements and venous blood samples were obtained. In these studies, subcutaneous abdominal adipose tissue was taken from all subjects (n=28 healthy study; n=27 surgical study), and visceral adipose tissue was obtained from some of the surgical patients (n=14). In all studies, collagenase was used to isolate mature adipocytes from the adipose tissue, and FAAH and MGL activities in the adipocytes were assayed using tritium labelled substrates. Human subcutaneous preadipocytes (Promocell, Germany) were cultured and differentiated. Adipocytes were cultured with high concentrations of glucose (15 mM) and/or insulin (1 μM) for 24 hours, in combination with anandamide or 2-AG for 2 or 24 hours. Adiponectin, leptin and resistin in the cell culture media were then measured using sandwich ELISAs. In another study, anandamide and 2-AG uptake were measured in differentiated adipocytes after 2 or 24 hours’ stimulation with glucose and/or insulin. FAAH and MGL activities in the cultured adipocytes were also measured in this study. In rats, FAAH and MGL activities correlated with body mass. In healthy humans, FAAH activity in subcutaneous adipocytes correlated with BMI and waist circumference, but not with other anthropometric measurements, serum glycaemic markers or adipokines. In obese patients, the enzyme activities had no relationships with any of the anthropometric or metabolic markers investigated. Furthermore, there were no differences in activity between patients with metabolic syndrome or diabetes and those without. In both rats and humans, there were no significant differences in FAAH and MGL activities between subcutaneous and visceral adipocytes. In the cell culture studies, anandamide and 2-AG did not alter adipokine secretion under normal, high glucose or high insulin conditions. Chronic insulin exposure increased anandamide uptake, but none of the other acute or chronic treatments with glucose and/or insulin affected anandamide or 2-AG uptake. Glucose and insulin were found to reduce MGL activity. These studies suggest that the rate of anandamide hydrolysis in mature adipocytes is increased in obesity. This relationship was not apparent in a morbidly obese sample. MGL activity in humans does not have relationships with adiposity or metabolic markers, and this may reflect its role as a major component of lipid metabolism, particularly lipolysis. Anandamide and 2-AG are unlikely to be direct mediators of adipokine secretion, at least in cell culture. Insulin may affect endocannabinoid signalling in adipocytes by increasing anandamide uptake and suppressing MGL activity. Overall, these results support the notion that the ECS in adipocytes is dysregulated in obesity, but this is not driven by specific factors associated with obesity.